Hospital Admissions Due to Heart Failure in A Tertiary Greek General Hospital - In the Era of COVID-19 - Chrysohoou, Christina; Tsioufis, Konstantinos; Leontsinis, Ioannis; Kariori, Maria; Dalakouras, Ioannis; Charalambus, Georgios; Papanikolaou, Aggelos; Tolis, Panagiotis; Fragoulis, Christos; Pan, Demosthenes (Cardiology and Cardiovascular Medicine, 2020)
The aim of the present study was to explore hospital admissions due to heart failure in the cardiology department of a tertiary General Hospital in Athens, Greece, that does not hospitalize SARS-CoV-2 infected patients. The daily number of admissions at Cardiology Wards and Cardiology Intensive Care Unit were retrieved from hospital’s database (January 1st – April 30th, 2018, 2019 and 2020). The visits at the hospital were significantly reduced by 41.1% in March 2020 and by 32.7% in April 2020 as compared to January (p for linear trend <0·001). As the number of confirmed COVID-19 cases increased in Greece (i.e., from February 26th to April 2nd) the number of visits decreased (p=0.01), whereas, the opposite observed in the period afterwards (p=0.01). The number of admitted heart failure patients in March 2020 was the lowest compared to the entire period (n = 43 cases vs. 95%CI 53-92, p<0·001), whereas the number of those admitted in April was higher compared to March, but still lower compared to the entire studied period (n = 56 cases, p<0·001). However, although hospital admissions due to heart failure showed a declining trend following the overall admissions observed during the COVID-19 period, the percent of heart failure patients among all those admitted in March and April 2020 was 17% and 20%, respectively, and was higher compared to January and February of the same year, as well as the highest throughout the entire studied period 2018 – 2020 (range from 13% to 20%).